Analisis Pengaruh Investasi Dan Jumlah Penduduk Yang Bekerja Terhadap Pertumbuhan Ekonomi Sumatera Barat Tahun 2005-2020 - Dedi Julianto; Rishendri Mukhtar (Jurnal Penelitian Dan Pengkajian Ilmiah Sosial Budaya, 2022)
The title of the research is Analysis of the Effect of Investment and Total Working Population on Economic Growth in West Sumatra in 2005 – 2020. This study aims to analyze the direct or indirect effect of the number of working people and investment on economic growth in West Sumatra during the period 2005-2020. The method used in this study is the Ordinary Least Square (OLS) method in seeing the effect of the independent variable on the dependent variable. Here the dependent variable is economic growth, namely the amount of GDP at constant prices in 2010, and the independent variable is investment and the number of working people. Furthermore, to see the causal effect of investment and the number of people working on economic growth, it can be written in the form of a non-linear regression equation. From the analysis results obtained the equation Ln Y = 1 + 2 ln I + 3 ln L+ U . From the regression equation, it can be seen that: 2 is the coefficient of elasticity of investment on economic growth and 3 is the coefficient of elasticity of the working population on economic growth in West Sumatra. the 2019 covid pandemic. In the period after the covid pandemic there was also a positive relationship between labor and investment on the economic growth of the West Sumatra region. However, economic growth has decreased compared to the pre-covid period. During the analysis period, the natural growth of the West Sumatran economy fluctuated with an average GRDP growth of 7.28% per year.